Food, health, and exercise - Human Relation Media (New York: Human Relation Media, 2002)
This video discussed about food guide pyramid, nutritional labels and exercise which is benifitial into our lives.
Executive producer, Anson W. Schloat ; consultant, Ellie Krieger
Keywords: Nutrition; Exercise; Diet; Health education